Impact of chronic pain on driving behaviour: a systematic review. Issue 3 (March 2022) - Vaezipour, Atiyeh; Oviedo-Trespalacios, Oscar; Horswill, Mark; Rod, J.E.; Andrews, Nicole; Johnston, Venerina; Delhomme, Patricia
Abstract : Abstract: Driving is a complex task that requires both the ability to rapidly identify potential hazards and respond appropriately to driving situations to avoid crashing. A great deal of research has sought to increase road safety by focusing on risky behaviours, very few of which have explored the effects of chronic pain (CP) on driving behaviour. This systematic review aimed to assess driving behaviour and motor vehicle crash risk in drivers with CP. Four databases (Embase, PubMed, Scopus, and PsycINFO) were searched using relevant search terms. From 8543 studies, 22 studies met the eligibility criteria for inclusion in this review. A driving behaviour framework, based on the Michon model of driving behaviour, is proposed to map the effect of CP on driving behaviour. Findings suggest that drivers with CP engage in risk-compensatory strategies that are positive from a precautionary perspective. However, there is considerable variability in the use of such strategies across different samples, suggesting that there are significant barriers and facilitators involved in these decisions. Moreover, our findings provide some evidence that CP could increase crash risk and change driving behaviour. Evidence-based recommendations for practitioners and policymakers are proposed regarding the risks of driving in individuals experiencing CP. Future research into CP in driving could benefit from having a unified evidence-based approach to determine behaviour at all levels of the driving task. Abstract : Supplemental Digital Content is Available in the Text.